STUDI ANATOMIS DAN HISTOLOGIS PANKREAS BIAWAK AIR (Varanus salvator) (Anatomical and Histological Study of the Pancreas of Water Monitor Lizard (Varanus salvator)) - Hamny Hamny; Muhammad Iqbal; Sri Wahyuni; Mustafa Sabri; M. Jalaluddin; Rinidar Rinidar (Jurnal Kedokteran Hewan, 2016)
The aim of this research was to determine the anatomy and histology of pancreas of water monitor lizard (Varanus salvator). Two pancreas were used in this research (a male and a female). Water monitor lizard was euthanized using chloroform and subsequently necropsied to collect the pancreas. The pancreas was washed in 0.9 % NaCl solution. Anatomical observations were carried out including location, shape, and color of pancreas, also the length and weight measurements. Then, pancreas was fixed with 4% paraformaldehyde for 7 days to proceed to histological preparation and hematoxylin eosin (HE) staining. The results of the anatomical observations showed that pancreas of water monitor lizard have two lobes, dorsal lobe (splenic lobe) and ventral lobe (duodenal lobe). Dorsal lobe which was in oval form adhered with the spleen, and ventral lobe was located in the cranial of intestines with the form of long spherical. Both of pancreas lobes were white-yellow color with the length of 1.45±0.64 cm (dorsal lobe) and 7.00±0.42 cm (ventral lobe). Weight of dorsal lobe was 0.15±0.01 g and ventral lobe was 6.35±2.30 g. The histological observations found the acinar cells, ducts, and blood vessels in both of pancreas lobes. Additionally, the similar structure of Langerhans islet only found at the ventral lobe of pancreas. In conclusion, pancreas of water monitor lizard consists of two lobes which located differently. Ventral lobe is larger than the dorsal lobe. Both lobes have similar histological structure except the Langerhans islets are only appeared in the ventral lobe.